The effects of listening-reading programme on the pronunciation of English words by form one students from a secondary school in Pahang - Yusra, Rosli; Pilus, Zahariah (2015)
Listening –Reading (LR) activity is an alternative approach to the teaching and learning of reading and pronunciation in the ESL classroom. The activity involves simultaneous listening and reading of story books whereby readers not only read but also listen to the pronunciation of the same words contained in the texts being read by native speakers. To find out whether the activity is effective in developing pronunciation skill or not, the activity was implemented on a group of Form One students in Pahang for six months. The San Diego Quick Assessment (SDQA) was used as a pre and post- test to measure the students' ability in pronuncing English words. Result from the Paired-samples T-test shows that there is a significant difference in students’ pronunciation performance before and after the implementation of the LR activity (t=-2.75, df=35. p≤ .05). Majority of the students (50%) improved by 1 to 2 points in the posttest; however, 38.89% did not show any improvement. The remaining 11.11% of the students however, showed deterioration in their posttest achievement.